Book Review: Anirban Das, Towards Politics of the (IM)Possible: The Body in Third World Feminism. (March 2015) - Patel, Vibhuti
Anirban Das, Towards Politics of the (IM)Possible: The Body in Third World Feminism, London, Anthem Press, 2012, 232 pp., $99, ISBN 9781843318552.